Aproximación didáctica a la poesía a través de la música. - García Carcedo, Pilar (Didáctica. Lengua y Literatura, 1999)
In order to exemplify a possible strategy for a didactic approach to poetry, to its rhythm and music, we have chosen one of the latest and less known sonnets of Blas de Otero: «El Bolero», which is an homage to Maurice Ravel's composition. Starting from a musical audition previous to the expressive reading, we propose 43 Pilar García carcedo Aproximación didáctica a la poesía a través de la música analysing the rhythmic impression to discover the stylistic procedures used by the poet to achieve the imitative description of Ravel's composition. The access to the poem through the music is the final purpose of this work, because often and specially in the world of childhood, the reader or hearer of poetry is attracted mainly by rhyíhm, melody, alliterations and other phonic or rhythmic resources.
Keywords: Poeuy Music Rhythm Sonnet Didactic approach Musical audition Encouragement fo expressive reading Stylistic; rhythmic and phonic